Community Development Associations And Rural Development In Plateau And Imo States In Nigeria. A Case Study Of Social Capital And People Empowerment - Lere, Ishaku Bitrus (2010)
The main objective of this research is to explore first, the factors that limit community development associations contributions to rural development in Plateau state and second, the reasons that allow Community Development Associations (CDAs) in Imo to perform better than CDAs in Plateau State despite their similar economic and demographic characteristics.